Effect of demonstration method on learning success - Philippe Tohon Loiser; Wanye Endne (International Journal of Curriculum Development, Teaching and Learning Innovation, 2022)
The purpose of teaching carried out in the classroom according to Mager is to focus on student behavior or performance as a type of out put that exists in students and can be observed and shows that these students have carried out learning activities. Thus the alternative hypothesis formulated has been able to know the truth in this research so that it can be taken as a conclusion from this study, namely that "The demonstration method applied in learning has had a real influence, in the sense that it can be relied upon as a good method for teaching. As one of the alternative learning methods that can activate students, the demonstration method can be applied in the classroom which is expected to increase the level of thinking and experience of students, especially if students are expected to practice about a material that is understood.